Graphic Design and Visual Creation: The flipped classroom in remote learning in academic journalism education. - Bianchini Ferreira Pedrini, Jociene Carla; Domingos de Almeida, Cristóvão; Dallaqua Pedrini, Igor Aparecido (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2023)
This article presents a case study exploring the remote learning experience of the Graphic Planning and Visual Creation classes of a journalism course offered at the Araguaia Campus of Universidade Federal de Mato Grosso, Brazil. This study focused on the second semester of 2021 during the COVID-19 pandemic, when the active learning methodology of the flipped classroom was employed in these classes. Using a qualitative and descriptive approach, we analyze the experience of teaching practical subjects — normally taught in person in university labs using specific software programs — in a remote setting without hampering the teaching–learning process. In this case study, the students and professors used Canva as an innovative learning method to effectively create high-quality advertising and journalistic works.
Capítulo completo en acceso abierto que hace parte de la obra Media and information literacy for the public good: UNESCO MILID Yearbook 2023.
Keywords: Planificación gráfica; Creación visual; Aprendizaje remoto; Aula invertida; Educación periodística; 374.0124; Graphic planning; Visual creation; Remote learning; Flipped classroom; Journalism education; Literacy (Education) — Case Studies; Primary Education; Education and Development; Vocational Training; Media Literacy; Adult Literacy — Research